Influence of infiltration regimes on hydrocarbon accumulation processes in Northern part of West Siberia - A. V. Goreva (Известия высших учебных заведений: Геология и разведка, 2022)
Background. Hydrogeological analysis is necessary for a comprehensive forecast of oil and gas deposits in any region. Early in the development of petroleum hydrogeology in the 1940–1970s, conditions for hydrocarbon (HC) accumulation were actively examined at depths of about 1–2 km, where meteoric waters often occur. However, for a long time, there was no interest in exploring petroleum basin infiltration systems despite the colossal hydrocarbon resources in West Siberia, Alberta (Canada), the Norwegian-Danish oil and gas basin (Norway) and Jungar Banner (China), which are associated with an infiltration hydrodynamic regime (IHR). The resumption of research into hydrocarbon systems controlled by IHR is advisable for theoretical and advanced applications in the exploration of hydrocarbon deposits, including non-structural hydrocarbon accumulation. This is essential for oil and gas fields with a long well production history, where the resources of hydrocarbon deposits associated with anticline structures have largely been exhausted.Aim. To elaborate on the influence of IHR on the HC accumulation processes, the evolution and preservation of these accumulations in the Northern part of West Siberia.Results. The authors discussed features of the infiltration system of the Northern part of the West Siberian hydrogeological basin and proved its unity within the onshore and offshore regions. It was shown that a specific feature of this basin consists in an internal discharge zone associated with the Gulf of Ob in modern plans. Based on analysis of hydrodynamic potentials within the Albian-Cenomanian complex, local accumulations of hydrocarbons, formed in the absence of control from the structural factor, were revealed.